Potential for Developing Educational Tourism Based on The Genealogy and History of The Walisongo in Java - Susanto, Dedy; Mawahib, Muhammad Zainal; Anasom, Anasom; Istiqlaly, Ahmad Syauqi; Hakim, Lukmanul; Saerozi, Saerozi (Munazzama: Journal of Islamic Management and Pilgrimage, 2024)
This study highlights the potential for educational tourism based on the history and genealogy of Walisongo in Java, which could have been more optimal. Walisongo has an important role in spreading Islam and Javanese culture, but its appeal to educational tourism still needs to be expanded. This study explores how historical sites, genealogies, and life stories of Walisongo can be used as the main attraction, as well as the obstacles and opportunities in developing this tourism. This study used qualitative methods to collect data from literature and interviews with the community, historians, and stakeholders. Secondary data from books, journals, and articles related to Walisongo were also analyzed to provide a complete picture of the potential of Walisongo's cultural heritage. The study results indicate that Walisongo has great appeal for educational tourism, especially among students interested in studying the history of the spread of Islam in Java. However, several obstacles exist, such as minimal supporting facilities, lack of infrastructure, and limited effective promotion. In addition, the need for more public understanding of the history of Walisongo requires more comprehensive educational materials. This study recommends the development of educational tourism based on Walisongo that can support cultural preservation and provide economic benefits for the local community.